PERMODELAN SISTEM PENGENDALIAN INTERNAL BAGI LKM: PERLUASAN PERANAN AUDIT INTERNAL DALAM PROSES STRATEGI BISNIS - Nia Tresniati (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2015)
Microfinance institutions have specified characteristic in management process which are particularly related to customer characteristics and society social culture. Therefore, planning and business strategy process have own their characteristics. It’s implicated to strategy management process, operational system & procedure and internal control. In accordance with some studies from microfinance experts, the scope of internal control in finance institutions have restricted within risk management context, internal audit functions have only to monitor the operational activities and to measure the risks. Management use internal audit information for their management decisions that caused by risk. Actually, internal audit has wide and important role which considered to business strategy process in business entity. Furthermore, good health internal control should have been included risk management. Even though microfinance institutions at the middle downward to micro scale, internal audit should have been still on their function. Therefore, internal audit functions are considered essential role in internal control system for business strategy process. The methodology in this study use model of Internal control system. The internal control system model based on literature and observation by the author